(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Termites play important roles in the ecosystem as detritivores and soil engineers. However, alterations of the forest could change the diversity and abundance of termites. The Agropark at Universiti Malaysia Kelantan (UMK), Jeli Campus is an agricultural park that is surrounded by secondary forest and rubber plantations. This study was conducted to determine the diversity and pest species composition of termites at Agropark, UMK. Standardized line transects 100m long × 2m wide and divided into 20 sections (5m long × 2m wide) were conducted at three different sampling sites in May to September 2015. A total of 29 termite species from 13 genera were successfully identified with relative abundance of 128 (total hits). Diversity indices show high diversity and evenness among the termite species in the study area. The termites comprise of family Termitidae (75.9%) and family Rhinotermitidae (24.1%). Subfamily Macrotermitinae recorded higher a number of species (12 species, 78 hits) compared to other subfamilies recorded in this study. Wood feeders and epigeal mound builders dominated the termite assemblages. The total pest termite species collected is 41.4% (12 species) while 58.6% (17 species) of termite species were non-pest species that provide good ecological services to Agropark, UMKKJ. The pests are mainly from genera Coptotermes, Schedorhinotermes, Macrotermes, Microtermes and Globitermes. The higher number of pest species shows the possibility of pest attacks to the buildings around the Agropark. Precautions against termite attack should be taken earlier to prevent serious damage to buildings in the future.